2016
DOI: 10.1080/14767058.2016.1208742
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Bakri balloon tamponade on the rate of postpartum hysterectomy for uterine atony

Abstract: Our findings show that utilization of the Bakri balloon is associated with a decreased rate of postpartum hysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…in the presence of accreta, other studies attempting to evaluate the impact of the Bakri balloon on peripartum hysterectomy rates would exclude accreta from the calculations. 25 A limitation of the present study is its retrospective nature.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…in the presence of accreta, other studies attempting to evaluate the impact of the Bakri balloon on peripartum hysterectomy rates would exclude accreta from the calculations. 25 A limitation of the present study is its retrospective nature.…”
Section: Discussionmentioning
confidence: 93%
“…Our data concurred with such observations. Owing to the high failure rates in the presence of accreta, other studies attempting to evaluate the impact of the Bakri balloon on peripartum hysterectomy rates would exclude accreta from the calculations …”
Section: Discussionmentioning
confidence: 99%
“…oxytocin administration), intrauterine tamponade (e.g. a Bakri balloon or Sengstaken–Blakemore tube), interventional radiology, uterine artery ligation, hysterectomy, and uterine compression sutures (UCSs) …”
Section: Introductionmentioning
confidence: 99%
“…a Bakri balloon or Sengstaken-Blakemore tube), interventional radiology, uterine artery ligation, hysterectomy, and uterine compression sutures (UCSs). [2][3][4][5][6] Since B-Lynch sutures were first reported in 1997, 7 various methods of uterine compression suturing have been proposed and have yielded good outcomes, with hemostasis rates of 76%-100%. 8 However, a few studies have reported that use of UCSs can lead to changes in fertility and might have effects on subsequent pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…Intrauterine balloon tamponade has been suggested as an effective, easily administered minimally invasive treatment option to control uterine bleeding while preserving the mother's ability to bear additional children [46]. In terms of mechanism of action, the intrauterine balloon is believed to act by exerting inward to outward pressure against the uterine wall, resulting in a reduction in persistent capillary and venous bleeding from the endometrium and the myometrium [47].…”
Section: Uterine Balloon Tamponadementioning
confidence: 99%